(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Cerebrovascular Accident is the second commonest cause of death worldwide. Cerebrovascular Accident is sudden death of brain cells due to lack of oxygen when the blood flow to the brain is impaired by blockage or rupture of an artery. It is the chronic disease and also a major cause of long-term disability and has potentially enormous emotional and socio economic consequences for patients, and their families. So the study was conducted to assess the effectiveness of Health empowerment programme on level of knowledge and practice regarding care of patient with CVA. The main objectives are to assess the pretest level of knowledge and practice regarding care of patient with cerebrovascular Accident, and to determine the effectiveness of Health empowerment programme on the level of knowledge and practice among care givers of patient with cerebrovascular Accident. A quantitative research approach and pre experimental, one group pre test, post test design was chosen to assess the level of knowledge and practice regarding Health empowerment programme conducted at, Government General Hospital, Chennai, caregivers of patients with cerebrovascular Accident who satisfied the inclusive criteria were selected as samples using purposive sampling technique. A health empowerment programme comprising a power point teaching, demonstration and reinforcement regarding health empowerment programme formed the intervention of the study. The pre and post-test level of knowledge and practice was assessed using structured questionnaire and observational check list respectively. The findings of the study revealed that the pre test mean score of knowledge was 6.73 with S.D of 2.11 and the post-test mean score of knowledge was 13.45 with S.D of 1.57 The calculated ‘t’ value of 25.68 was found to be statistically highly significant.